Inteligencia emocional en el trabajo - Goleman, Daniel; Cherniss, Cary (BookaVivo, 2021)
How does emotional intelligence as a competency go beyond the individual to become something that a whole group or organization can build and use collectively? Written primarily by members of the Research Consortium on Emotional Intelligence in Organizations, founded by renowned EI experts Daniel Goleman and Cary Cherniss, this groundbreaking compendium examines the conceptual and strategic issues involved in defining, measuring, and promoting emotional intelligence in organizations. . The book's contributing authors share fifteen models that have been field-tested and empirically validated in existing organizations. They also detail twenty-two guidelines for promoting emotional intelligence and describe a variety of measurement strategies to assess emotional and social competence in organizations.